2019
DOI: 10.1021/acs.langmuir.9b00456
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Tricolor Emission-Based White Light from Supramolecular Organic–Inorganic Hybrid Gel

Abstract: The development of engineered hybrid systems by encapsulating nanoparticles in gel scaffolds and their synergistic effects are highly crucial for the fabrication of advanced functional materials. Herein, a series of dipeptides containing an aromatic amino acid at the N-terminal and an aliphatic amino acid at the C-terminal were synthesized and studied. Among them, only the dipeptide L-Phe-L-Val can form both hydro-and organogelator, depending on the N-and C-terminal protecting groups. The organogel shows brigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The other similar analogs of dipeptides, such as Boc-Tyr-Aib, Boc-Trp-Aib, Boc-Phe-Ala ( Sangeetha and Maitra, 2005 ), Boc-Phe-Gly ( O’Leary et al, 2011 ), and Boc-Aib-Phe, have all failed to form such a hydrogel under the same condition. Haldar and the coworkers have found out that the N-Boc-protected dipeptide Boc-Phe-Val could form a hydrogel in the mixtures of NH 4 OH and NaCl; Na 2 CO 3 and LiOH; and NaCl and KOH ( Podder et al, 2019 ). This result suggested that sodium and hydroxide ions both played a key role in hydrogel formation.…”
Section: Cooh-terminal and N-terminal Modified Dipeptidementioning
confidence: 99%
“…The other similar analogs of dipeptides, such as Boc-Tyr-Aib, Boc-Trp-Aib, Boc-Phe-Ala ( Sangeetha and Maitra, 2005 ), Boc-Phe-Gly ( O’Leary et al, 2011 ), and Boc-Aib-Phe, have all failed to form such a hydrogel under the same condition. Haldar and the coworkers have found out that the N-Boc-protected dipeptide Boc-Phe-Val could form a hydrogel in the mixtures of NH 4 OH and NaCl; Na 2 CO 3 and LiOH; and NaCl and KOH ( Podder et al, 2019 ). This result suggested that sodium and hydroxide ions both played a key role in hydrogel formation.…”
Section: Cooh-terminal and N-terminal Modified Dipeptidementioning
confidence: 99%
“…In principle, combinations of two or three types of different colors are necessary for generating white light. Therefore, in the material design, the key point is to maintain a color balance suitable for white emission. So far, several strategies have been proposed, such as encapsulation into micelles or vesicles, host–guest interactions, fixation into gels, and arrangement with metal–organic frameworks. White-light emission from a single luminophore has been also realized by the assortment of different emission mechanisms. …”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular polymers are emerging materials that are bonded through dynamic noncovalent bonds. They have excellent mechanical properties and received extensive attention in the field of polymer science. UPy is a self-complementary supramolecular group with a quadruple hydrogen bond structure and has a high binding constant, which has been widely used in the fields such as supramolecular synthesis, shape memory materials, self-healing materials, hydrogels, self-assembly, biomedicine, and others. , Polyethylene glycol (PEG) is a commonly used polymeric plasticizer, which has also proven to show a toughening effect to the polymeric matrixes. Based on this, we first terminated one hydroxyl group of PEG with UPy groups to prepare UPy–PEG–OH, then isocyanated it by reacting with HDI, and finally grafted it onto the surface of exfoliated mica to form UPy–PEG-modified mica nanoflakes. Through the vacuum-assisted self-assembly, a relatively dense UPy–PEG-modified mica paper is formed, as shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%